Integration the Low Cost Camera Images with the Google Earth Dataset to Create a 3D Model - Marwa Mohammed Bori; Zahraa Ezzulddin Hussein (Salehan Institute of Higher Education, 2020)
As known Close range photogrammetry represents one of the most techniques to create precise 3D model. Metric camera, digital camera, and Laser scanning can be exploited for the photogrammetry with variety level of cost that may be high. In this study, the cost level is taken in to consideration to achieve balance between the cost and the obtained accuracy. This study aims to detect potential of low cost tools for creating 3D model in terms of obtained accuracy and details and comparing it with corresponding studies. Smart phone camera is the most available for everyone; this gave the motivation for use in this study. In addition, Google Earth was used to integrate the 3D model produced from all sides including the roof. Then, two different types of the mobile camera were used in addition to the DSLR camera (Digital Single Lens Reflex) for comparison and analysis purposes. Thus, this research gave flexibility in work and low cost resulting from replacement the metric camera with the smart camera and the unmanned aerial vehicle (UAV) with Google Earth data. Mechanism of the work can be summarized in four steps. Firstly, photogrammetry planning to determine suitable baselines from object and location of targets that measured using GPS and Total station devices. Secondly, collect images using close range photogrammetry technique. Thirdly, processing step to create the 3D model and integrated with Google Earth images using the Agi Photoscan software. Finally, Comparative and evaluation stage to derive the accuracy and quality of the model obtained from this study using statistical analysis method. Regarding this Study, University of Baghdad, central library was selected as the case study. The results of this paper show that the low cost 3D model resulted from integrating phone and Google Earth images gave suitable result with mean accuracy level reached to about less than 5 meters compared with DSLR camera result, this may be used for several applications such as culture heritage and architecture documentation.